Exploring ethical dilemmas and institutional challenges in AI adoption: a study of South African universities - Muringa, Tigere Paidamoyo (Frontiers in Education, 2025)
IntroductionArtificial intelligence tools like ChatGPT and DeepSeek are increasingly shaping higher education. However, their integration into student learning remains underexplored. This study investigates how university students in South Africa use AI-based tools in their academic practices and the specific tasks these tools support. It also examines the ethical challenges and considerations arising from their use, highlighting the need for structured institutional guidelines.MethodsA qualitative approach was employed, involving in-depth semi-structured interviews with 50 students from four South African universities.ResultsFindings reveal that students widely but informally use AI tools for tasks such as essay writing and assignment preparation. The absence of formal institutional guidance has led to ethical ambiguities and inconsistent usage practices.DiscussionThe study accentuates the urgency for universities to develop institutional AI frameworks. These frameworks should promote the responsible and effective use of AI tools while addressing academic support needs and ethical considerations in higher education.